Digital studio tutors as partners - Branham, Cassandra Ann; Blomstrom, Sally; Mumpower, Lori; Kissh, Kimberly; Wiley, Jaclyn; Liu, Yunxiao; Miller, Kody; Bryant, Zachary; Reedy, Brian (International Journal for Students as Partners, 2019)
This case study examines an initiative at a STEM-focused university where a Digital Studio was developed in response to a perceived lack of digital literacies among students. Digital Studio tutors partnered with faculty, students, and the Center for Teaching and Learning Excellence to improve instruction and enhance students’ communication and digital literacy skills. Digital Studio tutors acted as partners in several ways, including developing training materials, conducting on-campus outreach, and contributing to curriculum development and content delivery in a Speech course. Ultimately, we observed that positioning Digital Studio tutors as partners enhanced the learning experience for all involved. The tutors’ skills, knowledge, and approaches complemented those of the faculty member to help students achieve the learning outcomes of the course, while also allowing the tutors and the faculty director to enhance their own digital literacy skills through their involvement in the Digital Studio.